2013
DOI: 10.4238/2013.december.11.3
|View full text |Cite
|
Sign up to set email alerts
|

A new tetra-primer ARMS-PCR for genotyping bovine kappa-casein polymorphisms

Abstract: ABSTRACT. Kappa-casein (κ-casein) is one of the most abundant milk proteins. Its main function is to avoid the aggregation of casein micelles, keeping them, and therefore calcium phosphate, in pockets in solution. In bovines, a κ-casein functional polymorphism has been associated with fat, calcium, and protein milk contents and faster curd contraction in cheese production. Quicker curd contraction reduces the loss of milk solids, enhancing cheese yield. This polymorphism induces a double amino acid substituti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 10 publications
0
15
0
1
Order By: Relevance
“…The DNA extraction method affects the outcome of T-ARMS PCR (Medrano and de Oliveira 2014). Various authors have undertaken different approaches to overcome these difficulties and successfully generated T-ARMS genotyping (Medrano and de Oliveira 2014; Fonseca et al 2013; Ahlawat et al 2014; Singh et al 2014). …”
Section: Resultsmentioning
confidence: 99%
“…The DNA extraction method affects the outcome of T-ARMS PCR (Medrano and de Oliveira 2014). Various authors have undertaken different approaches to overcome these difficulties and successfully generated T-ARMS genotyping (Medrano and de Oliveira 2014; Fonseca et al 2013; Ahlawat et al 2014; Singh et al 2014). …”
Section: Resultsmentioning
confidence: 99%
“…The present study reported the usefulness of T-ARMS PCR genotyping to detect CVM for the first time. T-ARMS PCR-based genotyping was published for other important mutations in livestock [ 25 28 ], including our report on Bovine Leukocyte Adhesion Deficiency (BLAD) testing [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it can be concluded that this method is an efficient, as well as sufficient option for detection. 25 …”
Section: Discussionmentioning
confidence: 99%